ChemInform Abstract: Transition Metal Complexes Supported by Highly Basic Imidazolin‐2‐iminato and Imidazolin‐2‐imine N‐Donor Ligands. Issue 16 (22nd April 2014) - Wu, Xian; Tamm, Matthias
Abstract Review: 186 refs.